The Rise of Feminism in the Works by Henry James: Some Narratological Insights - Boyarkina, Iren (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
James’ fiction crosses many of the artificially imposed borders and often deals explicitly with social changes and their consequences, for example, the emerging role and power of women in society. James was among the first American writers to introduce feministic issues into his works. This paper explores the theme of feminism in “The Turn of the Screw”, “The Jolly Corner" and The Bostonians emphasizing that in the latter James raises the problem of possibility for women of their simultaneous self-realization in family, at work, and in social life. This is still one of the most burning issues in feministic writing thus making James relevant in the 21st century. Analysing The Bostianians and shorter works by Henry James, the paper demonstrates that the writer pays a lot of attention to the issues of female personal freedom and self-realization determined by the loyalty to the institution of marriage. James depicts the growing tendency of alienation and misunderstanding between men and women, underlined in his short works and The Bostonians.
Keywords: Henry James; feminism; gender roles; gender studies; narratology; narratological analysis